Drop Vertical Jump Landing Mechanics Are Similar Between Patients With Quadriceps Tendon and Patellar Tendon Autografts After Anterior Cruciate Ligament Reconstruction - Jennifer Hunnicutt, Ph.D., A.T.C.; Hannah Collins, B.S.; Michelle McLeod, Ph.D., A.T.C.; Chris Gregory, Ph.D., P.T.; Harris Slone, M.D.; Kate Pfile, Ph.D., A.T.C. (Arthroscopy, Sports Medicine, and Rehabilitation)
Purpose: To compare the biomechanics of a drop vertical jump (DVJ) landing task and functional outcomes among patients with anterior cruciate ligament reconstruction (ACLR) with quadriceps tendon (QT) and patellar tendon (PT) autografts. Methods: Physically active patients who underwent primary ACLR with either a QT or PT autograft were included in this study. All were within 6 months to 2 years after surgery and cleared for return to physical activity. Subjects completed DVJs in a biomechanics laboratory. Peak vertical ground reaction force (VGRF) and lower-extremity joint sagittal and frontal plane kinematics and kinetics were collected and analyzed. Mann-Whitney U tests were used to compare the surgical limbs of the QT and PT autograft groups for kinematic and kinetic variables. Wilcoxon rank-sum tests were used to compare the surgical and nonsurgical limbs for both the QT and PT autograft groups. Results: Twenty-four physically active individuals who underwent primary ACLR with QT (n = 14) or PT (n = 10) autografts completed DVJs in a biomechanics laboratory. There were no statistically significant biomechanical differences between the QT and PT groups. Peak VGRF differed between the surgical and nonsurgical limbs for the QT (surgical and nonsurgical, 1.10 and 1.30 N) and PT (surgical and nonsurgical, 1.10 and 1.35 N) groups. Specifically, both groups demonstrated lower VGRFs in the surgical limb compared with the nonsurgical limb (P < .05). Additional medium and large effect sizes were found when comparing kinetic variables between limbs within both surgical groups. Conclusions: Regardless of the graft-specific surgical technique, patients who undergo ACLR are returning to activity with movements that resemble an offloading pattern of the surgical limb. Coupled with the finding of an absence of differences in kinematic and kinetic variables between the QT and PT autograft groups suggests that the QT graft may be a viable alternate graft source for ACLR. Level of Evidence: Level III, retrospective comparative study.